Metabolite profiling identifies the mycotoxin alternariol in the pathogen Stagonospora nodorum - Tan, Kar-Chun; Trengove, R.; Maker, G.; Oliver, Richard; Solomon, P. (Springer Science+Business Media, 2009)
A recent comparative proteomics study identified the short-chain dehydrogenase (Sch1) as being required for asexual sporulation (Tan et al. Eukaryotic Cell 7:1916–1929, 2008). Metabolite profiling was undertaken on the mutant strains of Stagonospora nodorum lacking the Sch1 gene to help elucidate its role. Gas chromatography-mass spectrometry of the polar metabolites in the Sch1 mutants identified a secondary metabolite at a 200-fold greater concentration than observed in the wild-type strains. Comparative analysis of the secondary metabolite and the mycotoxin alternariol using ESI-MS/MS confirmed the identity of the compound as alternariol. This is the first report to confirm the presence of a mycotoxin in S. nodorum and compelling the field to consider the health implication of this disease.